Aspects de l' interface syntaxe/sémantique: le cas des verbes à /complexité - Bazenga, Aline (2020)
The /complexity/ feature (Blanche-Benveniste et al. 1987) incorporates a class of French verbs known as 'symmetric' verbs (rivaliser, cohabiter), 'reciprocal' verbs (s'entraider) without, however, being restricted solely to those classes (cf. grouiller, amonceler, succeder, grouper, etc). This feature induces a 'plural' reading of the entity formed by the verbal lexeme and the syntactic positions it creates. In this paper, we intend to put forward a new descriptive format for such verbs, using the notion of 'verbs operators' (cf. Bach et al. 1995) and based on a combination of lexical, syntactic and semantic criteria (derivationaI affixes, Prep-Constructions, Se-Constructions, Coordination).